Differences in anthropometry, biological age and physical fitness between young elite kayakers and canoeists - Lopez-Plaza, D.; Alacid, F.; Muyor, J. M.; Lopez-Minarro, P. A. (Journal of Human Kinetics, 2017)
The aim of this study was to determine the anthropometric and physical characteristics of youth elite paddlers and to identify the differences between kayakers and canoeists. A total of 171 male paddlers (eighty-nine kayakers and eighty-two canoeists), aged 13.69 ± 0.57 years (mean ± SD) volunteered to participate in this study. The participants completed basic anthropometric assessments (body mass, stretch stature, sitting height, body mass index, maturity level, sum of 6 skinfolds and fat mass percentage) as well as a battery of physical fitness tests (overhead medicine ball throw, counter movement jump, sit-and-reach and 20 m multi-stage shuttle run tests). The anthropometric results revealed a significantly larger body size (stretch stature and sitting height) and body mass in the kayakers (p < 0.01) as well as a more mature biological status (p = 0.003). The physical fitness level exhibited by the kayakers was likewise significantly greater than that of the canoeists, both in the counter movement jump and estimated VO2max (p < 0.05), as well as in the overhead medicine ball throw and sit-and-reach test (p < 0.01). These findings confirm the more robust and mature profile of youth kayakers that might be associated with the superior fitness level observed and the specific requirements of this sport discipline.